Correction to: Valuch, Tibor. “Following the Life Stories of Participants in the 1956 Hungarian Revolution.” Hungarian Cultural Studies. e-Journal of the American Hungarian Educators Association, Volume 9 (2016) DOI: 10.5195/ahea.2016.253 - Tibor Valuch (Hungarian Cultural Studies, 2017)
The dates next to the names of two interviewees, Imre Lázár and Zoltán Mervó, were shown incorrectly. The original article can be found via the DOI: http://dox.doi.org/10.5195/ahea.2016.253